A thousand metagenome-assembled genomes of Akkermansia reveal phylogroups and geographical and functional variations in the human gut - Lv, Qing-Bo; Li, Shenghui; Zhang, Yue; Guo, Ruochun; Wang, Yan-Chun; Peng, Yongzheng; Zhang, Xiao-Xuan (Frontiers in Cellular and Infection Microbiology, 2022)
Akkermansia muciniphila has long been considered to be the only Akkermansia species in the human gut and has been extensively studied. The present study revealed the genomic architecture of Akkermansia in the human gut by analyzing 1,126 near-complete metagenome-assembled genomes, 84 publicly available genomes, and 1 newly sequenced Akkermansia glycaniphila strain from the human gut. We found that 1) the genomes of Akkermansia were clustered into four phylogroups with distinct interspecies similarity and different genomic characteristics and 2) A. glycaniphila GP37, a strain of Akkermansia, was isolated from the human gut, whereas previously, it had only been found in python. Amuc III was present in the Chinese population, and Amuc IV was mainly distributed in Western populations. A large number of gene functions, pathways, and carbohydrate-active enzymes were specifically associated with phylogroups. Our findings based on over a thousand genomes strengthened our previous knowledge and provided new insights into the population structure and ecology of Akkermansia in the human gut.